2009
DOI: 10.1680/macr.2008.61.6.389
|View full text |Cite
|
Sign up to set email alerts
|

Combination of mechanical and optical profilometry techniques for concrete surface roughness characterisation

Abstract: Achieving durable bond between new and old concrete still represents a challenge in concrete repair technology. It has been the subject of a number of investigations, but in most cases, only adhesion strength was addressed. To better understand bond mechanisms, in particular those related to surface roughness, two complementary surface characterisation techniques were implemented, providing a multiscale roughness characterisation by means of specific filtering calculations: mechanical profilometry for low-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Results obtained for laser profilometry and optomorphology are different in values while the same SRI: this is due to the fact that the filtration of the signal was not applied in case of optomorphology. This was already observed in previous research [23]. However, conclusions remain the same: the higher SRI increases, the higher Pa.…”
Section: Fig2 Sand Test For Surface Roughness Evaluationsupporting
confidence: 87%
See 3 more Smart Citations
“…Results obtained for laser profilometry and optomorphology are different in values while the same SRI: this is due to the fact that the filtration of the signal was not applied in case of optomorphology. This was already observed in previous research [23]. However, conclusions remain the same: the higher SRI increases, the higher Pa.…”
Section: Fig2 Sand Test For Surface Roughness Evaluationsupporting
confidence: 87%
“…Optomorphology, a technique of relief identification is based on the deformation's measurement of a parallel fringes pattern projected on a surface [24] and allows for a digitalization of the surface, as presented in Garbacz et al [11] showed that the surface geometry of the substrates tested is discriminated by similar parameters, whatever the filtration level is. Authors' investigations [16,23,24] show similar relationship for C40-A when comparing results of SRI and mean arithmetic deviation of total profile (Pa) obtained by optomorphology. Relation between Pa vs. SRI is presented in Figure 4.…”
Section: Fig2 Sand Test For Surface Roughness Evaluationmentioning
confidence: 65%
See 2 more Smart Citations
“…This is why the observations were completed with profilometry of the surface. Mechanical and optical profilometry are sometimes used on concrete to assess its roughness and evaluate its behavior regarding adhesion problems [3][4][5].…”
Section: Microtopographymentioning
confidence: 99%